An Integrated Geology-Mine-Plant and Eco-Efficiency Simulator for Anglo Platinum's Evaluation and Operational Improvement Initiatives (The Australasian Institute of Mining and Metallurgy, 2010)
An Integrated Geology-Mine-Plant and Eco-Efficiency Simulator for Anglo Platinum's Evaluation and Operational Improvement Initiatives